A unifying translational framework to advance treatment research for comorbid PTSD and substance use disorders. (August 2021) - Hien, Denise A.; López-Castro, Teresa; Fitzpatrick, Skye; Ruglass, Lesia M.; Fertuck, Eric A.; Melara, Robert
Highlights: Comorbid PTSD and substance use disorders (PTSD+SUD) is common and difficult to treat. We propose a framework to unify PTSD+SUD laboratory and treatment sciences. We review how PTSD+SUD disrupts four core neurofunctional domains, i.e. executive functioning, negative emotionality, reward salience, and social cognition. Identifying changes in these core domains can help personalize PTSD+SUD treatment. Abstract: We provide a unifying translational framework that can be used to synthesize extant lines of human laboratory research in four neurofunctional domains that underlie the co-occurrence of posttraumatic stress and substance use disorders (PTSD+SUD). We draw upon the Alcohol and Addiction Research Domain Criteria (AARDOC) to include executive functioning, negative emotionality, reward, and added social cognition from the National Institute of Mental Health (NIMH) Research Domain Criteria into our framework. We review research findings across each of the four domains, emphasizing human experimental studies in PTSD, SUD, and PTSD+SUD for each domain. We also discuss the implications of research findings for treatment development by considering new ways of conceptualizing risk factors and outcomes at the level of the individual patient, which will enhance treatment matching and advance innovations in intervention.